Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats - Xiao-Fei Wang; Tai-Yun Zhao; Rui-Bin Su; Ning Wu; Jin Li (Neuroscience Bulletin, 2016)

Index-based evaluation of vegetation response to meteorological drought in Northern China - Rui Li; Jing’ai Wang; Tianjie Zhao; Jiancheng Shi (Natural Hazards, 2016)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Brain structure–function associations identified in large-scale neuroimaging data - Zhi Yang; Jiang Qiu; Peipei Wang; Rui Liu; Xi-Nian Zuo (Brain Structure and Function, 2016)

Adenovirus-mediated shRNA interference against HSV-1 replication in vitro - Bo Song; Xinjing Liu; Qingzhi Wang; Rui Zhang; Ting Yang; Zhiqiang Han; Yuming Xu (Journal of NeuroVirology, 2016)

Loss of preferred habitat and pollen limitation threatens reproduction in a rare mountain Paeonia delavayi - Wei Li; Wen-wen Pan; Rui Tan; Juan Wang (Journal of Mountain Science, 2016)

Cross-species amplification of microsatellites in genera Megalobrama and Parabramis - RUI DU; DALONG ZHANG; YIZHOU WANG; WEIMIN WANG; ZEXIA GAO (Journal of Genetics, 2016)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

A monotonically declining elevational pattern of bacterial diversity in freshwater lake sediments - Jin Zeng; Dayong Zhao; Huabing Li; Rui Huang; Jianjun Wang; Qinglong L. Wu (Environmental Microbiology, 2016)
Summary The distribution patterns of bacterial communities along elevational gradients remain unexplored in aquatic ecosystems. This study investigated the diversity and community composition of bacteria in the sediments of lakes along a mountainside elevational gradient from 525 to 4 490 m in western China. The bacterial alpha diversity (taxonomic richness and phylogenetic diversity) at different sediment depths decreased monotonically with the increasing elevation, and the beta diversity (dissimilarity between lakes) increased significantly with the increasing elevation distance. Both elevation and chemical variables including pH and carbon/nitrogen ratio were identified as major factors affecting the bacterial diversity. Especially, bacterial alpha/beta diversity was significantly related to both chemical and elevational gradients in the surface sediments, whereas elevation overwhelmed chemical factors in influencing the bacterial alpha/beta diversity in the subsurface sediments. Phylogenetic structure analysis demonstrated that environmental filtering was the most important process affecting the bacterial community assembly along the elevational gradient, and the strength of environmental filtering increased towards high elevations. In summary, we observed for the first time a monotonically decreasing elevational pattern in bacterial diversity of freshwater lake sediments, which is mainly driven by elevation associated environmental factors.

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - Yong-ping Wang; Guo-yu Li; Hui-jun Jin; Lan-zhi Lu; Rui-xia He; Peng Zhang (Journal of Mountain Science, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

The ROS derived mitochondrial respirstion not from NADPH oxidase plays key role in Celastrol against angiotensin II-mediated HepG2 cell proliferation - Xin Liu; Rui-wei Gao; Miao Li; Chun-feng Si; Yong-peng He; Min Wang; Ying Yang; Qing-yin Zheng; Chao-yun Wang (Apoptosis, 2016)

Screening for cold-resistant tomato under radiation mutagenesis and observation of the submicroscopic structure - Shuai Wang; Rui Yang; Chang Shu; Xichun Zhang (Acta Physiologiae Plantarum, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Tissue Transglutaminase and Its Product Isopeptide Are Increased in Alzheimer’s Disease and APPswe/PS1dE9 Double Transgenic Mice Brains - Ji Zhang; Suqing Wang; Wei Huang; David A. Bennett; Dennis W. Dickson; Dengshun Wang; Rui Wang (Molecular Neurobiology, 2016)

Increasing the recovery of heavy metal ions using two microbial fuel cells operating in parallel with no power output - Xiaohui Wang; Jing Li; Zhao Wang; Hairti Tursun; Rui Liu; Yanmei Gao; Yuan Li (Environmental Science and Pollution Research, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Exogenous Abscisic Acid Alleviates Cadmium Toxicity by Restricting Cd2+ Influx in Populus euphratica Cells - Yansha Han; Shaojie Wang; Nan Zhao; Shurong Deng; Chenjing Zhao; Nianfei Li; Jian Sun; Rui Zhao; Huilan Yi; Xin Shen; Shaoliang Chen (Journal of Plant Growth Regulation, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Using isotopic, hydrogeochemical-tracer and temperature data to characterize recharge and flow paths in a complex karst groundwater flow system in northern China - Ziyong Sun; Rui Ma; Yanxin Wang; Teng Ma; Yunde Liu (Hydrogeology Journal, 2016)

Functional analysis of a chitinase gene during the larval-nymph transition in Panonychus citri by RNA interference - Wen-Kai Xia; Xiao-Min Shen; Tian-Bo Ding; Jin-Zhi Niu; Rui Zhong; Chong-Yu Liao; Ying-Cai Feng; Wei Dou; Jin-Jun Wang (Experimental and Applied Acarology, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Anomalous astronomical time-latitude residuals: a potential earthquake precursor - Hui Hu; You-Jin Su; Yi-Fei Gao; Rui Wang (Applied Geophysics, 2016)

A new epidioxy-tetracyclic triterpenoid from Poria cocos Wolf - Shiping Li; Zhixin Wang; Rui Gu; Yiwu Zhao; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2016)

PLD3 in Alzheimer’s Disease: a Modest Effect as Revealed by Updated Association and Expression Analyses - Deng-Feng Zhang; Yu Fan; Dong Wang; Rui Bi; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

Selection of rootstocks for better morphological characters and resistance to low-temperature stress in the sweet pepper cultivar ‘Hongxing No. 2’ - Chang Shu; Rui Yang; Likun Yin; Xizhen Ai; Shaohui Wang; Wenchao Zhao (Horticulture, Environment, and Biotechnology, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Dust aerosol properties and radiative forcing observed in spring during 2001–2014 over urban Beijing, China - Xingna Yu; Rui Lü; K. Raghavendra Kumar; Jia Ma; Qiuju Zhang; Yilun Jiang; Na Kang; Suying Yang; Jing Wang; Mei Li (Environmental Science and Pollution Research, 2016)

Selenium Deficiency Attenuates Chicken Duodenal Mucosal Immunity via Activation of the NF-κb Signaling Pathway - Zhe Liu; Yanpeng Qu; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2016)

An analysis of physiological index of differences in drought tolerance of tomato rootstock seedlings - Xuehui Yao; Rui Yang; Fukuan Zhao; Shaohui Wang; Changbao Li; Wenchao Zhao (Journal of Plant Biology, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Cloning and expression analysis of c-type and g-type lysozymes in yellow catfish (Pelteobagrus fulvidraco) - Fei Ke; Yun Wang; XiaoYao Cao; GaoWei Pan; Rui Geng (Genes & Genomics, 2016)

Tigecycline: Alone or in combination? - Yun Cai; Nan Bai; Xu Liu; Beibei Liang; Jin Wang; Rui Wang (Infectious Diseases, 2016)

Dietary exposure to lead of adults in Shenzhen city, China - Liubo Pan; Zhou Wang; Zhaoqiong Peng; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Nimal Pathiraja; Ying Xiao; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2016)

Magnetic effervescent tablet-assisted ionic liquid dispersive liquid–liquid microextraction of selenium for speciation in foods and beverages - Xiaojun Wang; Long Wu; Jiaqi Cao; Xincheng Hong; Rui Ye; Weiji Chen; Ting Yuan (Food Additives & Contaminants: Part A, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Submerged macrophytes shape the abundance and diversity of bacterial denitrifiers in bacterioplankton and epiphyton in the Shallow Fresh Lake Taihu, China - Zhou Fan; Rui-ming Han; Jie Ma; Guo-xiang Wang (Environmental Science and Pollution Research, 2016)

4-Nitrophenol induces activation of Nrf2 antioxidant pathway and apoptosis of the germ cells in rat testes - Yonghui Zhang; Yun Cao; Fei Wang; Meiyan Song; Xiaoli Rui; Yansen Li; ChunMei Li (Environmental Science and Pollution Research, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Variations of Nutrients in Gross Rainfall, Stemflow, and Throughfall Within Revegetated Desert Ecosystems - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (Water, Air, & Soil Pollution, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Extracellular ATP mediates cellular K+/Na+ homeostasis in two contrasting poplar species under NaCl stress - Nan Zhao; Shaojie Wang; Xujun Ma; Huipeng Zhu; Gang Sa; Jian Sun; Nianfei Li; Chenjing Zhao; Rui Zhao; Shaoliang Chen (Trees, 2016)

A new thalloid liverwort: Pallaviciniites sandaolingensis sp. nov. from the Middle Jurassic of Turpan–Hami Basin, NW China - Rui-Yun Li; Xue-lian Wang; Jing-Wei Chen; Sheng-Hui Deng; Zi-Xi Wang; Jun-Ling Dong; Bai-Nian Sun (PalZ, 2016)

Re: “PICALM Gene rs3851179 Polymorphism Contributes to Alzheimer’s Disease in an Asian Population” - Ming-Jie Wang; Rui-Ping Liu; Zhi-Jun Kong (NeuroMolecular Medicine, 2016)

Local fluid transfer regulation in heart extracellular matrix - Maria P. McGee; Michael J. Morykwas; James E. Jordan; Rui Wang; Louis C. Argenta (Journal of Physiology and Biochemistry, 2016)

Defense responses in female gametophytes of Saccharina japonica (Phaeophyta) induced by flg22-derived peptides - Bojun Lu; Dandan Li; Rui Zhang; Limei Shuai; Birgit Schulze; Peter G. Kroth; Dongmei Zhan; Gaoge Wang (Journal of Applied Phycology, 2016)

Impact of temperature variation between adjacent days on childhood hand, foot and mouth disease during April and July in urban and rural Hefei, China - Jian Cheng; Rui Zhu; Zhiwei Xu; Jinju Wu; Xu Wang; Kesheng Li; Liying Wen; Huihui Yang; Hong Su (International Journal of Biometeorology, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Soil microbial community composition and its driving factors in alpine grasslands along a mountain elevational gradient - Hai-jun Cui; Gen-xu Wang; Yan Yang; Yang Yang; Rui-ying Chang; Fei Ran (Journal of Mountain Science, 2016)

Slope spectrum variation in a simulated loess watershed - Fayuan Li; Guoan Tang; Chun Wang; Lingzhou Cui; Rui Zhu (Frontiers of Earth Science, 2016)

Phylogenetic analysis reveals that Japanese encephalitis virus genotype III is still prevalent in swine herds in Sichuan province in China - Rui Wu; Qiao Wang; Hongming Liu; Chunxia Chai; Bo He; Xiaobo Huang; Yiping Wen; Xintian Wen; Qiguai Yan; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2016)

A new triterpenoid saponin from Clinopodium chinense (Benth.) O. Kuntze - Biao Zeng; Guang-Da Liu; Bao-Bao Zhang; Shan-shan Wang; Rui Ma; Bei-Shan Zhong; Bai-qiu He; Yan Liang; Fei-Hua Wu (Natural Product Research, 2016)

Current approaches to reduce or eliminate mitochondrial DNA mutations - Liang Yang; Tingfang Mei; Xiaobing Lin; Haite Tang; Yi Wu; Rui Wang; Jinglei Liu; Zahir Shah; Xingguo Liu (Science China Life Sciences, 2016)

Culture of shoot tips from adventitious shoots can eradicate Apple stem pitting virus but fails in Apple stem grooving virus - Min-Rui Wang; Bai-Quan Li; Chao-Hong Feng; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

MicroRNA-1228* inhibit apoptosis in A549 cells exposed to fine particulate matter - Xiaobo Li; Zhen Ding; Chengcheng Zhang; Xin Zhang; Qingtao Meng; Shenshen Wu; Shizhi Wang; Lihong Yin; Yuepu Pu; Rui Chen (Environmental Science and Pollution Research, 2016)

Optimization of operation conditions for the mitigation of nitrous oxide (N2O) emissions from aerobic nitrifying granular sludge system - Rui-Ting Liu; Xin-Hua Wang; Yan Zhang; Ming-Yu Wang; Ming-Ming Gao; Shu-Guang Wang (Environmental Science and Pollution Research, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Upregulation of long noncoding RNA TMEVPG1 enhances T helper type 1 cell response in patients with Sjögren syndrome - Juan Wang; Huiyong Peng; Jie Tian; Jie Ma; Xinyi Tang; Ke Rui; Xinyu Tian; Yungang Wang; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

Global transcriptome profiling analysis reveals insight into saliva-responsive genes in alfalfa - Wenxian Liu; Zhengshe Zhang; Shuangyan Chen; Lichao Ma; Hucheng Wang; Rui Dong; Yanrong Wang; Zhipeng Liu (Plant Cell Reports, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

Bovine lactotroph cultures for the study of prolactin synthesis functions - Jianfa Wang; Zhanqing Yang; Shoupeng Fu; Bingrun Liu; Dianjun Wu; Wei Wang; Dongbo Sun; Rui Wu; Juxiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Treatment of retinitis pigmentosa due to MERTK mutations by ocular subretinal injection of adeno-associated virus gene vector: results of a phase I trial - Nicola G. Ghazi; Emad B. Abboud; Sawsan R. Nowilaty; Hisham Alkuraya; Abdulrahman Alhommadi; Huimin Cai; Rui Hou; Wen-Tao Deng; Sanford L. Boye; Abdulrahman Almaghamsi; Fahad Al Saikhan; Hassan Al-Dhibi; et al. (Human Genetics, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Azimuthal cement evaluation with an acoustic phased-arc array transmitter: numerical simulations and field tests - Xiao-Hua Che; Wen-Xiao Qiao; Xiao-Dong Ju; Rui-Jia Wang (Applied Geophysics, 2016)

Variation analysis of pathogenic Vibrio spp. and Pseudomonas spp. in Changhai mollusc farming waters using real-time PCR assay during 2011–2014 - Rui Liu; Limei Qiu; Xin Zhao; Huan Zhang; Lingling Wang; Zhanhui Hou; Dahai Gao; Linsheng Song (Marine Biology Research, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

A climatological comparison of column-integrated water vapor for the third-generation reanalysis datasets - Yu Wang; Ying Zhang; YunFei Fu; Rui Li; YuanJian Yang (Science China Earth Sciences, 2016)

Integrating a model with remote sensing observations by a data assimilation approach to improve the model simulation accuracy of carbon flux and evapotranspiration at two flux sites - TingLong Zhang; Rui Sun; ChangHui Peng; GuoYi Zhou; ChunLing Wang; QiuAn Zhu; YanZheng Yang (Science China Earth Sciences, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Comparison of diurnal dynamics in evaporation rate between bare soil and moss-crusted soil within a revegetated desert ecosystem of northwestern China - Ya-Feng Zhang; Xin-Ping Wang; Yan-Xia Pan; Rui Hu (Journal of Earth System Science, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Grazing modifies inorganic and organic nitrogen uptake by coexisting plant species in alpine grassland - Lili Jiang; Shiping Wang; Zhe Pang; Changshun Wang; Paul Kardol; Xiaoqi Zhou; Yichao Rui; Zhi chun Lan; Yanfen Wang; Xingliang Xu (Biology and Fertility of Soils, 2016)

Impact of climate change on regional irrigation water demand in Baojixia irrigation district of China - Xiao-jun Wang; Jian-yun Zhang; Mahtab Ali; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Zhuo Jiang (Mitigation and Adaptation Strategies for Global Change, 2016)

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

UV photolysis for enhanced phenol biodegradation in the presence of 2,4,6-trichlorophenol (TCP) - Jiaxiu Song; Wenbing Wang; Rongjie Li; Jun Zhu; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

A Chromone-Derived Schiff-Base Ligand as Al3+ “Turn on” Fluorescent Sensor: Synthesis and Spectroscopic Properties - Chao-rui Li; Jing-can Qin; Bao-dui Wang; Long Fan; Jun Yan; Zheng-yin Yang (Journal of Fluorescence, 2016)

Gas-phase ammonia and PM2.5 ammonium in a busy traffic area of Nanjing, China - Wenxin Wang; Shanshan Wang; Jianhua Xu; Rui Zhou; Chanzhen Shi; Bin Zhou (Environmental Science and Pollution Research, 2016)

On the development of a coupled regional climate–vegetation model RCM–CLM–CN–DV and its validation in Tropical Africa - Guiling Wang; Miao Yu; Jeremy S. Pal; Rui Mei; Gordon B. Bonan; Samuel Levis; Peter E. Thornton (Climate Dynamics, 2016)

Adaptation to climate change impacts on water demand - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; En-hong Guan; Yong-xiang Wu; Juan Gao; Rui-min He (Mitigation and Adaptation Strategies for Global Change, 2016)

Assembly and characterization of the MHC class I region of the Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) - Rui Ruan; Xiao-Ling Wan; Yang Zheng; Jin-Song Zheng; Ding Wang (Immunogenetics, 2016)

Cryopreservation for retaining morphology, genetic integrity, and foreign genes in transgenic plants of Torenia fournieri - Jing-Wei Li; Hou-Hua Li; Ren-Rui Wang; Xiao-Xia Gao; Qiao-Chun Wang (Acta Physiologiae Plantarum, 2016)